Proportional integral derivative-based aneroid sphygmomanometer testing method - Wuwus Ardiatna; Nurdina Gita Pratiwi; Siddiq Wahyu Hidayat; Prayoga Bakti; Asep Rahmat Hidayat; Ihsan Supono (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
One of the parameters to be tested on the sphygmomanometer is the deflection of the dial. The testing method based on the standard uses manual air pressure to increase the pressure so that the dial is pointed to the desired pressure. This paper proposed an automatic testing method using a proportional-integral-derivative (PID) controller based on arduino to control the pressure. The result shows that the system is not suitable to use. The process capability index at each given setpoint is less than 1. This low cost proposed testing method still needs to be improved and could become an alternative solution for laboratory testing of the sphygmomanometer.